The nature of language planning in colonial Bengali: A reading on Bankimchandras Bangla Bhasha - Azam, Mohammad (Dhaka University Journal of Linguistics, 2009)
The essay Bangla Bhasha' (Bengali Language) by Bankimchandra Chatterjee was first published in Bangadarshan', Joistho 1285 issue. In those days, an ongoing debate by the scholars on the acceptable style' of Bengali prose was brought out in different magazines and periodicals. In this debate, there were, generally two groups? one was Sanskritpanthi' (proponent of Sanskrit) which according to Bankim, was Prachinponthi' (backward looking) group; and the other was Banglapanthi' (proponent of Bengali) who, according to Bankimchandra was Nabyapanthi' (New group). Bankimchandra asserted that it is auspicious to adopt the middle-path' by way of setting aside the advice of the both groups? old and new. The Language analysts of later generation, almost without any exception, looked at this claim' with a gesture of appreciation. In this article we try to grasp the nature and characteristics of Bankim`s middle path'. Dhaka University Journal of Linguistics Vol.1(1) 2008